Expanding syphilis testing: A scoping review of syphilis testing interventions among key populations - Ong, Jason J. (Expert Rev Anti Infect Ther, 2018)
INTRODUCTION: Syphilis is an important sexually transmitted infection (STI). Despite inexpensive and effective treatment, few key populations receive syphilis testing. Innovative strategies are needed to increase syphilis testing among key populations. AREAS COVERED: This scoping review focused on strategies to increase syphilis testing in key populations (men who have sex with men (MSM), sex workers, people who use drugs, transgender people, and incarcerated individuals). EXPERT COMMENTARY: We identified many promising syphilis testing strategies, particularly among MSM. These innovations are separated into diagnostic, clinic-based, and non-clinic based strategies. In terms of diagnostics, self-testing, dried blood spots, and point-of-care testing can decentralize syphilis testing. Effective syphilis self-testing pilots suggest the need for further attention and research. In terms of clinic-based strategies, modifying default clinical procedures can nudge physicians to more frequently recommend syphilis testing. In terms of non-clinic based strategies, venue-based screening (e.g. in correctional facilities, drug rehabilitation centres) and mobile testing units have been successfully implemented in a variety of settings. Integration of syphilis with HIV testing may facilitate implementation in settings where individuals have increased sexual risk. There is a strong need for further syphilis testing research and programs.